Characteristics of Tweets from @realDonaldTrump in Early 2020 - Whissell, Cynthia (Advances in Social Sciences Research Journal, 2020)
This research examines the tweeting behavior of US president Donald Trump during the early crisis months of 2020. A study of 1507 tweets posted in January-April 2020, and a comparison of these to tweets from the first year of his presidency (2017) led to several statistically significant conclusions. Overall, the language of the tweets remained somewhat positive or pleasant. Trump’s tweets were both longer and much more frequent in 2020 (the rate rose from 7 to 30 per day). The pleasantness of the language in tweets was negatively related to their popularity (popular tweets used relatively unpleasant language). The president’s tweeting behavior modified somewhat (e.g. fewer hourly tweets) in conjunction with the coronavirus crisis and the abrupt decline of the markets in March. The tweets gave evidence of a distinctly Trumpian vocabulary that favored words and phrases such as “great”, “hoax”, and “fake news media”.